Analysis of the protective efficacy of approved COVID-19 vaccines against Omicron variants and the prospects for universal vaccines - Chen, Keda; Zhang, Ling; Fang, Zhongbiao; Li, Jiaxuan; Li, Chaonan; Song, Wancheng; Huang, Zhiwei; Chen, Ruyi; Zhang, Yanjun; Li, Jianhua (Frontiers in Immunology, 2023)
By the end of 2022, different variants of Omicron had rapidly spread worldwide, causing a significant impact on the Coronavirus disease 2019 (COVID-19) pandemic situation. Compared with previous variants of severe acute respiratory syndrome coronavirus 2 (SARS–CoV-2), these new variants of Omicron exhibited a noticeable degree of mutation. The currently developed platforms to design COVID-19 vaccines include inactivated vaccines, mRNA vaccines, DNA vaccines, recombinant protein vaccines, virus-like particle vaccines, and viral vector vaccines. Many of these platforms have obtained approval from the US Food and Drug Administration (FDA) or the WHO. However, the Omicron variants have spread in countries where vaccination has taken place; therefore, the number of cases has rapidly increased, causing concerns about the effectiveness of these vaccines. This article first discusses the epidemiological trends of the Omicron variant and reviews the latest research progress on available vaccines. Additionally, we discuss progress in the development progress and practical significance of universal vaccines. Next, we analyze the neutralizing antibody effectiveness of approved vaccines against different variants of Omicron, heterologous vaccination, and the effectiveness of multivalent vaccines in preclinical trials. We hope that this review will provide a theoretical basis for the design, development, production, and vaccination strategies of novel coronavirus vaccines, thus helping to end the SARS-CoV-2 pandemic.